1997
DOI: 10.1002/(sici)1099-0844(199709)15:3<181::aid-cbf737>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipid composition on rat liver nuclear membrane fluidity

Abstract: Nuclear membrane fluidity is measured in rat liver by use of the fluorescence anisotropy of two probes: diphenylhexatriene and its cationic derivative trimethylammonium-diphenylhexatriene. It has been shown that, in 2-month-old rat liver cells, the bilayer surface is less fluid than the hydrophobic core. The fluidity was higher in 6-day-old rat liver nuclei, in which both the amount of cholesterol and the cholesterol/phospholipid ratio decreased. The influence of the single phospholipids, and in particular of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 70 publications
2
14
0
2
Order By: Relevance
“…This in turn modulates the ratio of saturated to unsaturated fatty acids in the cell membrane. This ratio is a key regulator of cell membrane fluidity and structural integrity (3,42). Alteration in the unsaturated fatty acid content in the membrane caused by changes in the SCD enzyme activity has been shown to control membrane fluidity (43).…”
Section: Discussionmentioning
confidence: 99%
“…This in turn modulates the ratio of saturated to unsaturated fatty acids in the cell membrane. This ratio is a key regulator of cell membrane fluidity and structural integrity (3,42). Alteration in the unsaturated fatty acid content in the membrane caused by changes in the SCD enzyme activity has been shown to control membrane fluidity (43).…”
Section: Discussionmentioning
confidence: 99%
“…Final phospholipid concentration was determined by the Stewart method (23). Anionic liposomes were formed by egg phosphatidylcholine, egg phosphatidylglycerol, and cholesterol (8:1:1 molar ratio) to reproduce the charged lipid and cholesterol content of the nuclear membrane (24). Neutral liposomes were formed by phosphatidylcholine and cholesterol (9:1 molar ratio).…”
Section: Methodsmentioning
confidence: 99%
“…The possibility that PC can be transported by speci¢c protein inside the nucleus cannot be excluded, as well as that other minor pathways may be used for its synthesis. The complex of base exchanges has been detected in nucleus [11]. It has been shown that the content of PC may change inside the nucleus in many physiological situations, suggesting some rapid mechanisms with respect to the transport from the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear pellet still contains some rRNA which completely disappears after two washings in Barnes et al solution [20]. The nuclei were checked for possible cytoplasmic contamination also by evaluating the activity of a microsomal marker (NADH-cytochrome c-reductase) [11]. The swelling of nuclei and chromatin extraction were performed according to the method of Shaw and Huang [22], modi¢ed by Viola Magni et al [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation